Allogeneic adipose‐derived mesenchymal stem cell therapy in dogs with refractory atopic dermatitis: clinical efficacy and safety. (1st December 2018) - Villatoro, Antonio José; Hermida‐Prieto, Manuel; Fernández, Viviana; Fariñas, Fernando; Alcoholado, Cristina; Rodríguez‐García, M Isabel; Mariñas‐Pardo, Luis; Becerra, José
Abstract : Canine atopic dermatitis (AD) is a common skin disease with a 10–15 per cent prevalence. Current treatments vary in their efficacy and safety. The immunomodulatory properties of mesenchymal stem cells (MSCs) make them a promising alternative treatment. The aim of this study was to evaluate the therapeutic efficacy and safety of allogeneic canine adipose MSCs (cAd‐MSCs) in dogs with refractory AD. Twenty‐six dogs, suffering from AD for at least 12 months, not responding to conventional therapy, received an intravenous dose of 1.5×10 6 cAd‐MSCs/kg bodyweight. Clinical signs, haematological and biochemistry profiles, and AD severity were assessed in a six‐month follow‐up using a validated scoring system (Canine Atopic Dermatitis Extent and Severity Index, version 4 (CADESI‐04)). The degree of pruritus was quantified using a validated visual analogue scale, and also owner's global assessment of treatment efficacy. Twenty‐two animals completed the study. Pruritus and CADESI‐04 scores decreased significantly after one week or month of treatment, respectively, and remained stable for six months. Owner's global assessment score was 2.15±1.15 for all the animals in the study. In conclusion, systemic administration of allogeneic cAd‐MSCs appeared to be a simple therapy with positive outcome in the remission of clinical signs for AD refractory to conventional medications, for at least six months and with no adverse events.